Preliminary analysis of knee stress in full extension landing - Makinejad, M.D.; Abu Osman, Noor Azuan; Wan Abas, Wan Abu Bakar; Bayat, M. (2013)
OBJECTIVE: This study provides an experimental and finite element analysis of knee-joint structure during extended-knee landing based on the extracted impact force, and it numerically identifies the contact pressure, stress distribution and possibility of bone-to-bone contact when a subject lands from a safe height. METHODS: The impact time and loads were measured via inverse dynamic analysis of free landing without knee flexion from three different heights (25, 50 and 75 cm), using five subjects with an average body mass index of 18.8. Three-dimensional data were developed from computed tomography scans and were reprocessed with modeling software before being imported and analyzed by finite element analysis software. The whole leg was considered to be a fixed middle-hinged structure, while impact loads were applied to the femur in an upward direction. RESULTS: Straight landing exerted an enormous amount of pressure on the knee joint as a result of the body's inability to utilize the lower extremity muscles, thereby maximizing the threat of injury when the load exceeds the height-safety threshold. CONCLUSIONS: The researchers conclude that extended-knee landing results in serious deformation of the meniscus and cartilage and increases the risk of bone-to-bone contact and serious knee injury when the load exceeds the threshold safety height. This risk is considerably greater than the risk of injury associated with walking downhill or flexion landing activities.